Prevalence of Motor Difficulties in Greek Preschoolers: The Effect of Gender, Age, BMI, Place of Residence, and Hand Preference - Kechagia, Olga; Katartzi, Ermioni S.; Fotiadou, Eleni; Giagazoglou, Paraskevi (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
The main aim of the present study was to identify motor difficulties in Greek preschoolers. Secondary aims were to identify possible differences in prevalence of motor difficulties related to gender, age, body mass index, place of residence, and hand preference. 302 preschoolers were assessed using the first age band (3–6 years) of the Movement Assessment Battery for Children (2nd edition). The results showed high prevalence of significant (12.3%) and moderate (12.3%) motor difficulties in preschool children. Moreover, gender, age, BMI, residence, and hand preference effects showed no statistically significant differences (p > 0.05) and need further consideration among preschool children. However, there was evidence that some differences may exist between boys and girls, 4- and 5-year-old children, children with high and typical body mass index, children living in rural or urban areas, and right and left-handed children, regarding the occurrence of motor difficulties. These findings highlighted the need for early assessment in domains of motor development, such as hand dexterity, ball skills and balance in order for developmentally appropriate preschool physical education programs to be applied, with the aim to help preschoolers improve their difficulties and be physically active later in life.